Self-portrait with boy [compact disc, unabridged] : a novel - Lyon, Rachel (Simon & Schuster Audio, 2018)
One day, in the background of a self portrait, Lu accidentally captures on film a boy falling past her window to his death. The photograph turns out to be startlingly gorgeous, the best work of art she's ever made. It's an image that could change her life...if she lets it.